Manipulations to the Timing and Type of Instructions to Examine Motor Skill Performance Under Pressure - Ong, Nicole T.; Bowcock, Alison; Hodges, Nicola J. (Frontiers in Psychology, 2010)
There is evidence that prescriptive versus discovery methods of learning can lead to breakdowns under pressure due to “reinvestment” of knowledge and a more conscious, controlled mode of control. There is some speculation that this breakdown is mediated by the attentional focus of the instructions. We expected these effects to also be moderated by when in practice these instructions are given. Across two experiments, five groups practiced a forehand disc throwing task and we manipulated the timing and attentional focus of instructions. Internally-directed instructions provided to participants early in practice resulted in a slower rate of acquisition (outcome error) and detrimental effects under stress, in comparison to the same instructions provided later in practice or not at all. Externally-directed, technical instructions positively impacted rate of acquisition and regardless of when in practice they were provided, there were no adverse effects associated with instructions under pressure. These results show that the direction of attention encouraged by instructions moderates performance under stress as does the timing of presentation of these instructions.